The changing economic geography of companies and regions in times of risk, uncertainty and crisis - Neise, Thomas; Verfürth, Philip; Franz, Martin (The dynamics of economic space, 2025)
"This book offers conceptual and empirical insights from economic geography to explore how uncertainties, crises and risks, shape, reshape, and ultimately transform the spatial arrangements of companies and regions. This book provides valuable insights into the evolving landscape of economic interactions amidst contemporary challenges. It explores concepts such as global value chains, global production networks, regional resilience and the impact of crises, risks, and uncertainties on spatial economic patterns. Case studies from various regions, nations, and industries, including lesserresearched sectors such as medical technology and the restaurant and bar industry offer tangible and real world manifestations of these dynamics. Through its comprehensive coverage and interdisciplinary approach, this book equips readers with practical knowledge applicable to academia and real-world contexts. It offers a deeper understanding of the complex interplay between economic geography and contemporary challenges at a variety of levels. The book provides valuable perspectives for academics, practitioners, and policy makers in the fields of Economic Geography, Regional Studies, Political Sciences, Economic Sociology, Economics and International Business Studies"--